The Enhancement of Hawthorn Leaf Extracts on the Growth and Production of Short Chain Fatty Acids of Two Probiotic Bacteria - Khaleel, Sabah M.J.; Haddadin, Malik S.Y. (Pakistan Journal of Nutrition, 2013)
Hawthorn leaf extracts were prepared using water, ethanol and methanol and they were evaluated for their effects on the growth and metabolism of L. acidophilus and Bif. infantis in skim-milk. Ten concentrations of each extracts were used and highest counts of Bif. infantis and L. acidophilus were related to both concentration and the type of extract. All the three hawthorn leaf extracts increased cell counts over the control with no extracts. The level of 5 mg of (+) Catechin Equivalents (CE) per mL of the growth medium (100 mL) for all hawthorn leaf extracts samples had the most significant effect on the count of Bif. infants and L. acidophilus. The final values for the Short Chains Fatty Acids (SCFA), especially acetic acid secreted by L. acidophilus (2.30 gL-1), were significantly higher than those observed in milk alone. The ethanolic extract of hawthorn had significantly better effect on the growth of Bif. infantis and L. acidophilus than the other extracts, while water extract exhibited the lowest values. It is concluded that hawthorn leaf extracts showed growth-promoting and prebiotic activity on Bif. infantis and L. acidophilus and can be added to fermented milk to increase both the quality and the nutritional value of the final milk product and consequently human health.